Insights from zebrafish and mouse models on the activity and safety of ar-turmerone as a potential drug candidate for the treatment of epilepsy. - Adriana Monserrath Orellana-Paucar (Public Library of Science (PLoS), 2013)
In a previous study, we uncovered the anticonvulsant properties of turmeric oil and its sesquiterpenoids (ar-turmerone, α-, β-turmerone and α-atlantone) in both zebrafish and mouse models of chemically-induced seizures using pentylenetetrazole (PTZ). In this follow-up study, we aimed at evaluating the anticonvulsant activity of ar-turmerone further. A more in-depth anticonvulsant evaluation of ar-turmerone was therefore carried out in the i.v. PTZ and 6-Hz mouse models. The potential toxic effects of ar-turmerone were evaluated using the beam walking test to assess mouse motor function and balance. In addition, determination of the concentration-time profile of ar-turmerone was carried out for a more extended evaluation of its bioavailability in the mouse brain. Ar-turmerone displayed anticonvulsant properties in both acute seizure models in mice and modulated the expression patterns of two seizure-related genes (c-fos and brain-derived neurotrophic factor [bdnf]) in zebrafish. Importantly, no effects on motor function and balance were observed in mice after treatment with ar-turmerone even after administering a dose 500-fold higher than the effective dose in the 6-Hz model. In addition, quantification of its concentration in mouse brains revealed rapid absorption after i.p. administration, capacity to cross the BBB and long-term brain residence. Hence, our results provide additional information on the anticonvulsant properties of ar-turmerone and support further evaluation towards elucidating its mechanism of action, bioavailability, toxicity and potential clinical application.